Enhancing Bioactivity of Hydroxyapatite Scaffolds Using Fibrous Type I Collagen - Nitti, Paola; Kunjalukkal Padmanabhan, Sanosh; Cortazzi, Serena; Stanca, Eleonora; Siculella, Luisa; Licciulli, Antonio; Demitri, Christian (Frontiers in Bioengineering and Biotechnology, 2021)
In the field of bone tissue regeneration, the development of osteoconductive and osteoinductive scaffolds is an open challenge. The purpose of this work was the design and characterization of composite structures made of hydroxyapatite scaffold impregnated with a collagen slurry in order to mimic the bone tissue structure. The effect of magnesium and silicon ions enhancing both mechanical and biological properties of partially substituted hydroxyapatite were evaluated and compared with that of pure hydroxyapatite. The use of an innovative freeze-drying approach was developed, in which composite scaffolds were immersed in cold water, frozen and then lyophilized, thereby creating an open-pore structure, an essential feature for tissue regeneration. The mechanical stability of bone scaffolds is very important in the first weeks of slow bone regeneration process. Therefore, the biodegradation behaviour of 3D scaffolds was evaluated by incubating them for different periods of time in Tris-HCl buffer. The microstructure observation, the weight loss measurements and mechanical stability up to 28 days of incubation (particularly for HA-Mg_Coll scaffolds), revealed moderate weight loss and mechanical performances reduction due to collagen dissolution. At the same time, the presence of collagen helps to protect the ceramic structure until it degrades. These results, combined with MTT tests, confirm that HA-Mg_Coll scaffolds may be the suitable candidate for bone remodelling.